The role of novel antihyperglycaemic agents in the treatment of Type 2 diabetes - from glycaemic control to cardiovascular protection - Žunić, Tatjana; Ponjavić, Milojka (Archives of Pharmacy, 2020)
The advent of new antihyperglycaemic drugs has not only brought a greater variety of drugs used to control glycaemia, but has introduced changes in other important aspects of Type 2 diabetes (T2DM) therapy, cardioprotection and renoprotection. All new antihyperglycaemic drugs: sodium glucose co-transporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 receptor agonists (GLP-1 agonists), and dipeptidyl peptidase-4 (DPP-4) inhibitors were subjects of Cardiovascular Outcome Trials – CVOTs. Cardiovascular protection is not considered to be class specific, especially in the GLP-1 agonist group, but more likely drug specific. Based on the result of CVOTs, some drugs received from Food and Drug Administration labelled indications of reduction of the risk of major adverse cardiovascular events in adults with type 2 diabetes mellitus and established cardiovascular disease (liraglutide, semaglutide, dulaglutide, canagliflozin, empagliflozin, dapagliflozin). Cardiology and diabetology societies acknowledged CVOTs results in various ways. American Diabetes Associations (ADA) and European Association for the Study of Diabetes (EASD) still consider metformin as first-line drug but introduced precise criteria for utilization of GLP-1 agonists and SGLT2 inhibitors for primary as well as secondary cardiovascular (CV) prevention. The Canadian Diabetes Association (Diabetes Canada) recognized the use of an antihyperglycaemic agent with demonstrated CV outcome benefit in secondary prevention only. The European Society of Cardiology (ESC) favoured cardiovascular protection effects and chosen GLP-1 agonists and SGLT2 inhibitors to be first- line therapy in a treatment-naïve patient with atherosclerotic cardiovascular disease (ASCVD). National Institute for Health and Care Excellence (NICE) did not change the previous position of utilisation of novel antihyperglycemic drugs only for achieving adequate glycaemic control either as monotherapy when metformin is contraindicated or not tolerated or as add-on therapy in dual and triple combinations of antihyperglycemic drugs.